2022
DOI: 10.3390/ijms23062946
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nanocellulose to Produce Water-Based Conductive Inks with Ag NPs for Printed Electronics

Abstract: The need for more sustainable printed electronics has emerged in the past years. Due to this, the use of nanocellulose (NC) extracted from cellulose has recently been demonstrated to provide interesting materials such as functional inks and transparent flexible films due to its properties. Its high specific surface area together with the high content of reactive hydroxyl groups provide a highly tailorable surface chemistry with applications in ink formulations as a stabilizing, capping, binding and templating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, CNFs were used in combination with SDBS to enhance their dispersion potential and as a requirement for application in printed electronics. There are also different examples in which nanocellulose materials are used as an aqueous stabilizer of 0D metallic NPs, normally acting as a template during their synthesis [ 48 , 51 , 52 , 53 ]. For instance, it has been reported that TEMPO-oxidized CNCs grafted with amino groups were able to stabilize Ag NPs in water [ 51 ].…”
Section: Other Nanomaterials Dispersed Via Nanocellulosementioning
confidence: 99%
See 1 more Smart Citation
“…However, CNFs were used in combination with SDBS to enhance their dispersion potential and as a requirement for application in printed electronics. There are also different examples in which nanocellulose materials are used as an aqueous stabilizer of 0D metallic NPs, normally acting as a template during their synthesis [ 48 , 51 , 52 , 53 ]. For instance, it has been reported that TEMPO-oxidized CNCs grafted with amino groups were able to stabilize Ag NPs in water [ 51 ].…”
Section: Other Nanomaterials Dispersed Via Nanocellulosementioning
confidence: 99%
“…Furthermore, the size of Ag NPs was controlled by tuning the surface chemistry of CNCs, resulting in hybrid dispersions with different stabilities and morphologies. In a similar work, two different nanocellulose materials were employed: TEMPO-oxidized CNCs and carboxymethylated CNFs for the synthesis and stabilization of Ag NPs [ 52 ]. It was demonstrated that both nanostructures play two main roles: as a template for the Ag NPs synthesis and as an ink stabilizer for printed electronics.…”
Section: Other Nanomaterials Dispersed Via Nanocellulosementioning
confidence: 99%
“…Cellulose is a natural biopolymer found abundantly on Earth and is obtained from a vegetal source (annually, between 10 11 and 10 12 tons of nanocellulose are produced) [49]. The nanocelluloses are cellulose-based materials characterized by having nanoscale dimensions taken from plants, such as wood, coconut husk, sisal, algae, etc., or obtained from animals or bacteria [50,51]. They can be classified into three groups: (1) cellulose nanocrystals (CNCs), obtained chemically from plants or animals, (2) cellulose nanofibrils (CNFs), obtained mechanically, also from plants or animals, or (3) bacterial nanocellulose (BNCs), obtained from bacteria.…”
Section: Dielectric Inksmentioning
confidence: 99%
“…Koga et al prepared a carbon inkjet printer ink using CNTs and 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO)-oxidized CNFs dispersed in water [94]. Martinez-Crespiera et al formulated a water-based conductive ink with silver particles dispersed in nanocellulose [50].…”
Section: Polymeric Resin or Bindermentioning
confidence: 99%
“…On the other hand, the silicone surface is enriched with silicone oil, rendering it smoother and less prone to adhesion with other materials. [31,32] Currently, widely studied water-based conductive inks [33][34][35] face challenges in adhering to the surface of silicone. Materials with higher viscosity, such as conductive silver paste [36][37][38] and conductive silver adhesives, [39,40] can accumulate on the surface of silicone to form electrodes.…”
Section: Preparation and Electrical Performance Of Conductive Inkmentioning
confidence: 99%